Long term follow up of patients with endomyocardial fibrosis: effects of surgery. Issue 4 (1st April 1998) - Schneider, U; Jenni, R; Turina, J; Turina, M; Hess, O M
Abstract : Aims: To determine the long term outcome of patients with endomyocardial fibrosis and to compare echocardiographic and haemodynamic data before and after ventricular endocardial resection. Patients: Seventeen patients (11 women and six men; mean age 35.5 years) diagnosed with endomyocardial fibrosis at the University Hospital in Zurich, Switzerland from 1971 to 1995. Twelve patients (70%) had partial obliteration of both ventricles and in five patients (30%) the fibrotic lesions were limited to the left ventricle. Methods: Fourteen of the 17 patients had surgical resection: fibrosis was resected from both ventricles in five patients and from the left ventricle only in nine patients. Ten patients had mitral valve replacement and two had tricuspid valve replacement. Left ventricle endocardial resection was done without reconstruction or replacement of the atrioventricular valve in three patients. Preoperative and postoperatve echocardiographic data were available for 11 patients and haemodynamic data for six patients. Patients were followed up for 0.4–19 years (mean 8.6). Results: Preoperatively four patients were NYHA functional class IV and 10 were class III; postoperatively one patient was class III, seven class II, and six class I. Preoperatively, echocardiography showed obliteration of the left ventricular apex and inflow tract in all patients, which decreased or disappeared after surgery. Left ventricular end diastolic pressure decreased from 25 mm Hg before surgery to 14 mm Hg after successful resection of the fibrosis. Left ventricular end diastolic volume (normal 93 (17) ml/m 2 ) increased from 65 ml/m 2 to 97 ml/m 2 (p < 0.05) after surgery. Ejection fraction was normal preoperatively (57%) and decreased slightly (52%) after surgery. One patient died five months after surgery from heart failure. Four surgically treated patients died during the follow up period: one each from systolic dysfunction, recurrence of endomyocardial fibrosis, pneumonia, and food poisoning. Overall survival was 65% at five years and 59% at 10 years; the survival rates of the operated patients was 72% and 68%, respectively. Only one of the medically treated patients survived longer than three years from diagnosis. Conclusions: Endomyocardial fibrosis is a rare disease in European countries and is found mainly in women. The clinical picture is characterised by severe congestive heart failure but heart size is only moderately increased. Systolic performance is normal or only slightly depressed despite severe restriction to filling, atrioventricular valve regurgitation or both. Partial obliteration of the right and/or left ventricle may be detected by echocardiography. Endocardial resection with atrioventricular valve replacement is the treatment of choice with appreciable postoperative improvement and 10 year survival of approximately 70%.